Diseño Eléctrico del Centro de Control de Motores para la nueva PTAR de la Planta de Producción de Papelsa - Papeles y Cartones S.A, Ubicada en Barbosa Antioquia. (2020)
The new environmental regulations oblige the industries to comply with the minimum parameters of polluting residues towards the tributaries of the water, for this end the infrastructure of Papelsa does not have the capacity in its current plant, therefore, it must carry out the construction of a new, wastewater treatment plant, which must have an electrical system design to ensure its operation At the beginning of the project, a load study will be carry out according to the projection of the equipment to be installed, this data will allow the dimensioning of conductors, pipes, electrical protections and the equipment of the motor control center (MCC). The engineering of the project allows to obtain precise calculations of some subsystems that have a higher risk of failure, such as: the lightning protection system, the grounding system and the coordination of protections, with ensures a correct operation of the plant wastewater treatment. The cost of the project is determined from the electrical design and the technical characteristics of each equipment to be used, making a selection of the brand of equipment in general, Rockwell variable speed drives, ABB universal starters and general brand protections will be used. ABB and Schneider. The load required by the WWTP is 222 kVA, with most equipment at 480 V and 215 V and electrical wiring for XHHW-2 insulated AFD motors.